1998
DOI: 10.1096/fasebj.12.13.1331
|View full text |Cite
|
Sign up to set email alerts
|

In vitroreconstruction of a human capillary‐like network in a tissue‐engineered skin equivalent

Abstract: For patients with extensive burns, wound coverage with an autologous in vitro reconstructed skin made of both dermis and epidermis should be the best alternative to split-thickness graft. Unfortunately, various obstacles have delayed the widespread use of composite skin substitutes. Insufficient vascularization has been proposed as the most likely reason for their unreliable survival. Our purpose was to develop a vascular-like network inside tissue-engineered skin in order to improve graft vascularization. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
247
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(254 citation statements)
references
References 48 publications
6
247
0
1
Order By: Relevance
“…Their differentiation state prior to coimplantation with ECs, however, is an important parameter that supports the network, because the population that remained in an undifferentiated proliferated state formed stronger, more mature networks. The hMSCs fulfill at least two roles in supporting the vasculogenesis process, synthesis of trophic factors (22,23) and contributing the mural component (9,19,21,24,25), neither of which is well understood at present. Both in vitro and in vivo, the tubular networks formed by monocultures of ECs such as HUVECs are not stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their differentiation state prior to coimplantation with ECs, however, is an important parameter that supports the network, because the population that remained in an undifferentiated proliferated state formed stronger, more mature networks. The hMSCs fulfill at least two roles in supporting the vasculogenesis process, synthesis of trophic factors (22,23) and contributing the mural component (9,19,21,24,25), neither of which is well understood at present. Both in vitro and in vivo, the tubular networks formed by monocultures of ECs such as HUVECs are not stable.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo, the tubular networks formed by monocultures of ECs such as HUVECs are not stable. Inclusion of mesenchymal-derived cells that can serve as pericytes such as the 10T1/2 cell line, embryonic and dermal fibroblasts, or hMSCs generates networks that are more robust and can anastomose to form functional vessels in vivo (5,7,9,11,28). Furthermore, it is suggested that 10T1/2 cells differentiate into SMCs or pericytes through heterotypic interactions with ECs (10,11,13).…”
Section: Discussionmentioning
confidence: 99%
“…23 The 1:5 ratio of fibroblasts to ECs used in our previous study was based on previous reports in the literature. 6,12 However, the recent work by Melero-Martin et al…”
Section: Discussionmentioning
confidence: 99%
“…The cells should be clinically available, easy to purify and expand in vitro, and, ideally, autologous, thus avoiding host immune responses. Generation of functional vessels in vivo has been reported using mature ECs such as human umbilical vein ECs (HUVECs) 11,12 and human dermal microvascular ECs. 13 However, either these cells are unavailable for adults, or they require an invasive procedure to harvest.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts play an important role in organizing the clot, which includes the secretion of extracellular matrix and the promotion of angiogenesis. 14,15 To our knowledge, bi-layered prevascularized skin grafts so far have been only engineered based on the so-called ''self-assembly approach,'' [16][17][18] collagenbased scaffolds, 19,20 de-cellularized donor dermis, 21 or use of a de-cellularized porcine jejunal segment as suggested by Groeber et al 22 All of these methods are characterized by specific shortcomings: The self-assembly approach takes approximately 6 weeks to form a prevascularized neo-dermis, which is a significantly longer timeframe than our employed method. Collagen-based scaffolds, de-cellularized donor dermis, or xenogenous templates cannot offer a complete autologous approach; drawbacks such as transmission of infectious diseases, allergic reactions, or intricate experimental setup have to be taken into account as a possible future issue regarding human implementation.…”
Section: Discussionmentioning
confidence: 99%